Domestic Violence and Sexuality What's love got to do with it? - Donovan, Catherine (2014)
Available Open Access under CC-BY-NC-ND licence This book provides the first detailed discussion of domestic violence and abuse in same sex relationships, offering a unique comparison between this and domestic violence and abuse experienced by heterosexual women and men. It examines how experiences of domestic violence and abuse may be shaped by gender, sexuality and age, including whether and how victims/survivors seek help, and asks, what's love got to do with it? A pioneering methodology, using both quantitative and qualitative research, provides a reliable and valid approach that challenges the heteronormative model in domestic violence research, policy and practice. The authors develops a new framework of analysis - practices of love - to explore empirical data. Outlining the implications of the research for practice and service development, the book will be of interest to policy makers and practitioners in the field of domestic violence, especially those who provide services for sexual minorities, as well as students and academics interested in issues of domestic and interpersonal violence.